Consistency of higher order risk preferences - Cary Deck; Harris Schlesinger (Center for Economic Studies and ifo Institute (CESifo), 2012)
Risk aversion (a 2nd order risk preference) is a time-proven concept in economic models of choice under risk. More recently, the higher order risk preferences of prudence (3rd order) and temperance (4th order) also have been shown to be quite important. While a majority of the population seems to exhibit both risk aversion and such higher-order risk preferences, a significant minority does not. Rather than simply dismissing this behavior, we show how both risk-loving as well as risk-averse behaviors might be generated by a simple type of basic lottery preference for either (1) combining good outcomes with bad ones, or (2) combining good with good and bad with bad. We further show that this dichotomy is fairly robust at explaining higher order risk attitudes in the laboratory. In addition to our own experimental evidence, we take a second look at the extant laboratory experiments that measure higher order risk preferences and we find a fair amount of support for this dichotomy. Our own experiment is the first to look beyond 4th order risk preferences and we examine risk attitudes at even higher levels. The consistency of these results with expected utility theory and with a few non-expected utility theories is also examined.
Keywords: C90; D80; 330; risk apportionment; mixed risk aversion; mixed risk loving; prudence; temperance; edginess; laboratory experiments; moment preference; prospect theory; Risikopräferenz; Prospect Theory; Test